Three cases of a rare disease, congenital chloride diarrhea, summons up the variation in the clinical course and significance of early diagnosis and adequate treatment in the prevention of intellectual disability - Gürakan, Figen; Baysoy, Gökhan; Wedenoja, Satu; Uslu, Nuray; Ozen, Hasan; Ozaltin, Fatih; Höglund, Pia (The Turkish Journal of Pediatrics, 2011)
Congenital chloride diarrhea (CLD) (OMIM #214700) is a rare, autosomal recessive disease that is characterized by increased chloride loss in stool. As a result of electrolyte loss, surviving patients might have some complications, one of them being mental retardation. Here, we present three new Turkish patients with new mutations in the SLC26A3 gene. Although the clinical picture of the patients might be similar, consequences of the disease and complications might differ greatly among patients. Pediatricians should be aware of CLD as a potentially fatal or disabling disease if untreated. History of polyhydramnios, watery diarrhea, failure to thrive, poor growth, soiling, metabolic alkalosis and hypokalemia/hypochloremia should be an alarming set of findings for the diagnosis. Salt substitution therapy started early in life prevents early complications, allows normal growth and development, and favors good long-term prognosis.